Clinical and radiological predictors for persistent complaints five years after a lateral ankle sprain : A long-term follow-up study in primary care - Mailuhu, A. K.; Oei, E. H.; van Putte-Katier, N.; van Ochten, J. M.; Bindels, P. J.; Bierma-Zeinstra, S. M.; van Middelkoop, M. (Journal of Science and Medicine in Sport, 2018)
Objectives To examine the five-year prognosis and potential prognostic factors of patients with an acute lateral ankle sprain in primary care setting. Design Observational study. Methods 206 patients who participated in a cross-sectional study and visited their general practitioner with an acute lateral ankle sprain 6-12 months prior to inclusion were approached for a 5-year follow-up measurement consisting of an online questionnaire. At baseline patients completed standardized questionnaires, underwent a standardized physical examination and radiological examination (radiography and Magnetic Resonance Imaging) and scored their perceived recovery. Logistic regression analysis was used to examine potential predictive factors at baseline for the presence of persistent complaints after 5 years. Results 132 (64.1%) patients completed the 5-year follow-up. 18.2% reported persistent complaints and 30.3% had a re-sprain during follow-up. Baseline persistent complaints 6-12 months after an acute lateral ankle sprain (OR 6.38; CI 95% 1.54-26.44), dominant leg injury (OR 4.89; CI 95% 1.16-20.62) and a recurrent ankle sprain (OR 9.81; CI 95% 2.17-44.47) were significant predictors for persistent complaints 5 years after an acute ankle sprain. Physical examination and radiological findings did not add to the predictive value of the prognostic model. Conclusions Almost 20% of patients with an acute lateral ankle sprain experience persistent complaints after 5 years follow-up. Predictive factors for persistent complaints can be identified.